1995
DOI: 10.1177/000992289503400101
|View full text |Cite
|
Sign up to set email alerts
|

Lung Abscess in Infants and Children

Abstract: We retrospectively reviewed 18 cases of primary lung abscess and 10 cases of secondary lung abscess in infants and children during a 6-year period. Among 18 patients with primary abscesses, nine were boys and nine girls, from 9 months to 20 years old, but only two of 18 were less than 5 years old. Each had a solitary abscess. Location of abscesses included the right lower lobe (8), the right upper lobe (3), the left upper lobe (1), and the left lower lobe (6). One patient had Streptococcus pneumoniae bacteremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 7 publications
2
31
1
5
Order By: Relevance
“…However, both acute and chronic refractory pulmonary infections do occur. Previous reports have shown that a history of pneumonia is a major risk factor for the development of lung abscess or refractory lung infection [2,5]. Invasive procedures, like bronchoscopy to obtain material for bacteriologic studies, remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, both acute and chronic refractory pulmonary infections do occur. Previous reports have shown that a history of pneumonia is a major risk factor for the development of lung abscess or refractory lung infection [2,5]. Invasive procedures, like bronchoscopy to obtain material for bacteriologic studies, remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…4 The gold standard medical therapy for lung abscess is administration of empiric parenteral antibiotics with anaerobic bacteria and Gram-positive cocci coverage. 7 Early treatment can prevent further complications and can reduce the chance of obligatory surgical interventions. 7 In children, the role of surgical therapy for lung abscess should be limited only to a minority of patients who are refractory to medical treatment or who develop complications such as bronchopleural fistula.…”
Section: Discussionmentioning
confidence: 99%
“…7 Early treatment can prevent further complications and can reduce the chance of obligatory surgical interventions. 7 In children, the role of surgical therapy for lung abscess should be limited only to a minority of patients who are refractory to medical treatment or who develop complications such as bronchopleural fistula. 4 Lung abscess in children is a rare complication of M. pneumoniae infection and only four previous cases have been described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Akciğer apselerinin çoğu, spontan olarak bir bronşa drene olduğu ve kavite temizlendiği için sadece antibiyotik tedavisi ile düzelebilir ve çok az bir kısmı cerrahi drenaj gerektirir (35). Antibiyotik tedavisinde, kültür ve antibiyotik duyarlılık sonuçları tedavinin başarısını etkiler.…”
Section: Tanıunclassified